2020
DOI: 10.1039/c9gc03073e
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae: a sustainable adsorbent with high potential for upconcentration of indium(iii) from liquid process and waste streams

Abstract: Unmodified microalgal biomass grown on wastewater works as an effective and selective indium biosorbent even at low pH values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For the acidic solutions, HCQ removal was low to nil, with removal percentages of 4.76 ± 1.0% and 0.84 ± 0.4% for pH 5.12 ± 0.11 and 3.1 ± 0.1 respectively. This could be due to the high concentration of hydronium ions competing for binding sites on the biomass and limiting adsorption of HCQ (Nicomel et al, 2020) or to the destruction or dissociation of microalgal cells at acidic pH. From these results, it could be concluded that the optimal pH for better HCQ removal was pH = 9.9 ± 0.1.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For the acidic solutions, HCQ removal was low to nil, with removal percentages of 4.76 ± 1.0% and 0.84 ± 0.4% for pH 5.12 ± 0.11 and 3.1 ± 0.1 respectively. This could be due to the high concentration of hydronium ions competing for binding sites on the biomass and limiting adsorption of HCQ (Nicomel et al, 2020) or to the destruction or dissociation of microalgal cells at acidic pH. From these results, it could be concluded that the optimal pH for better HCQ removal was pH = 9.9 ± 0.1.…”
Section: Resultsmentioning
confidence: 98%
“…The control solutions showed that the transformation of HCQ could only take place in alkaline media (pH = 9.9 ± 0.1 and pH = 8.22 ± 0.08). At neutral and alkaline pH levels, there were more sites on the surface of the microalgae available for biosorption (Nicomel et al, 2020). For the acidic solutions, HCQ removal was low to nil, with removal percentages of 4.76 ± 1.0% and 0.84 ± 0.4% for pH 5.12 ± 0.11 and 3.1 ± 0.1 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional technologies have been used for In recovery from liquid processes and waste streams, but these conventional methodologies show many disadvantages, such as high requirements for reagents and energy, high capital and operational costs, generation of toxic waste products, and low recovery yield from low In concentration streams ( Nicomel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 They also present great potential as an eco-friendly alternative to synthetic adsorbents. 14 Various kinds of biopolymers have been reported as suitable biosorbents for uranium and rare earth metal ions, such as fungi (yeast (Saccharomyces cerevisiae) embedded cellulose, 25.9 mg g À1 for Eu 3+ ), 15 bacteria (Pseudomonas aeruginosa, 208 mmol g À1 dry biomass for La 3+ ) 16 and cellulose nanober (167 mg g À1 for UO 2…”
Section: Introductionmentioning
confidence: 99%